A cladistic analysis of the Stygnicranainae Roewer, 1913 (Arachnida, Opiliones, Cranaidae) - where do longipalp cranaids belong? - Orrico, Victor G. D. [UNESP]; Kury, Adriano B. (Wiley-Blackwell Publishing, Inc, 2009)
A character survey compiling the morphological information of the subfamily Stygnicranainae was carried out. Two new species of Stygnicranaus Roewer, 1913 are described from Colombia and the new genus Agathocranaus is described from Ecuador. All known species of the subfamily are included in a matrix of 46 morphological characters. Parsimony analysis under implied weights recovered a monophyletic Stygnicranainae including Tryferos Roewer, 1931 plus Stygnicranaus and Agathocranaus. However, the usage of the four subfamilies of Cranaidae as currently defined is abandoned because the two largest subfamilies of Cranaidae - Cranainae and Prostygninae - represent paraphyletic groups (grades), whereas Heterocranainae is a superfluous subfamily, including only the genus Heterocranaus Roewer, 1913. (C) 2009 The Linnean Society of London, Zoological Journal of the Linnean Society, 2009, 157, 470-494.
Keywords: Andes; cladistics; Colombia; Cranainae; Ecuador; Gonyleptoidea; Grassatores; Neotropics; Prostygninae; Venezuela